2017
DOI: 10.1377/hlthaff.2017.0083
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act Reduced Socioeconomic Disparities In Health Care Access

Abstract: The United States has the largest socioeconomic disparities in health care access of any wealthy country. We assessed changes in these disparities in the United States under the Affordable Care Act (ACA). We used survey data for the period 2011-15 from the Behavioral Risk Factor Surveillance System to assess trends in insurance coverage, having a personal doctor, and avoiding medical care due to cost. All analyses were stratified by household income, education level, employment status, and home ownership statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 33 publications
6
108
1
Order By: Relevance
“…[18][19][20][21][22][23] We describe the specific association of these variables with the use of surgery for NSCLC. County-level uninsured rate is known to have strong association with demographic and area-level socioeconomic factors, 17,24 and corrective measures mitigating adverse consequences of area-level socioeconomic factors can improve access to health services and outcomes. 22,25 For example, federal, state, and county policy initiatives such as Medicaid eligibility expansions, health-care safety nets, and public health programs targeting rural communities may enhance financial well-being, insurance coverage, and access to health care at the county level.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] We describe the specific association of these variables with the use of surgery for NSCLC. County-level uninsured rate is known to have strong association with demographic and area-level socioeconomic factors, 17,24 and corrective measures mitigating adverse consequences of area-level socioeconomic factors can improve access to health services and outcomes. 22,25 For example, federal, state, and county policy initiatives such as Medicaid eligibility expansions, health-care safety nets, and public health programs targeting rural communities may enhance financial well-being, insurance coverage, and access to health care at the county level.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ACA was enacted, studies have demonstrated that insurance coverage and health care access and utilization have improved across the country, particularly among groups that have historically had low levels of coverage, such as low-income individuals. 10 - 16 What is not well established, however, is how financial strain and vulnerability have improved as a result of the ACA’s increase in access, specifically with regard to different FPL groups. Other insurance expansion programs, such as the Massachusetts Health Reform and Oregon Health Insurance Experiment, have been shown that insurance reduced health-related financial stress.…”
Section: Introductionmentioning
confidence: 99%
“…The ACA is the largest scaled coverage and benefit expansion in the USA in recent years. The reform specifically targeted low‐ and moderate‐income adults, and has led to successful expansions of insurance coverage and improvements in healthcare access . Several major ACA provisions were also designed to address OOP affordability of health care.…”
Section: Discussionmentioning
confidence: 99%